Headache Management in Individuals with Brain Tumor - Cuneo, Ami; Murinova, Natalia (Seminars in Neurology, 2024)
Headache occurs commonly in individuals diagnosed with cerebral neoplasm. Though the features of a brain tumor-associated headache may vary, a progressive nature of headache and a change in headache phenotype from a prior primary headache disorder often are identified. Pathophysiologic mechanisms proposed for headache associated with brain tumor include headache related to traction on pain-sensitive structures, activation of central and peripheral pain processes, and complications from surgical, chemotherapeutic and/or radiotherapy treatment(s). Optimization of headache management is important for an individual's quality of life. Treatments are based upon patient-specific goals of care and may include tumor-targeted medical and surgical interventions, as well as a multimodal headache treatment approach incorporating acute and preventive medications, nutraceuticals, neuromodulation devices, behavioral interventions, anesthetic nerve blocks, and lifestyles changes.
Keywords: headache; brain tumor; headache treatment